Comparison between the conventional methods and Glasgow Benefit Plot in evaluating subjective hearing results after myringoplasty - Rayamajhi, P; Bhattaraj, H; Sinha, BK; Shrivastav, RP (Journal of Institute of Medicine Nepal, 2007)
Background: To compare the Conventional methods with Glasgow Benefit Plot in evaluating subjective hearing results after myringoplasty. Materials and Methods: Patients above 17 years of age with the diagnosis of Chronic Suppurative Otitis Media-tubotympanic type undergoing Myringoplasty at TU Teaching Hospital from January 2004 to July 2005 were included in the study. The pre and postoperative Pure Tone Audiometry (PTA) was performed and evaluated. The postoperative subjective hearing status of the patients was recorded as improved, same or worsened. Objectively, the postoperative hearing was assessed in terms of Air Bone Gap closure, Air Conduction Threshold improvement and Glasgow Benefit Plot. The objective methods were then compared with the postoperative subjective hearing status of the patients. Results: The association between the Air Bone gap closure and the postoperative subjective hearing status was not statistically significant. The association between the Air Conduction threshold improvement and the postoperative subjective hearing status was statistically significant. The association between the Glasgow Benefit Plot and the postoperative subjective hearing status was also statistically significant. Conclusion: The study showed that the Air Conduction threshold improvement and the Glasgow Benefit plot are better parameters for evaluating subjective hearing results after myringoplasty than the Air Bone gap closure. Key words: Glasgow Benefit Plot, myringoplasty, Pure Tone Audiometry (PTA) The full text of this paper is available at Journal of Institute of Medicine website